2000
DOI: 10.1021/tx0001124
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxy-2-nonenal and Ethyl Linoleate Form N2,3-Ethenoguanine under Peroxidizing Conditions

Abstract: In these studies, we demonstrate that N(2),3-ethenoguanine (N(2), 3-epsilonGua) is formed from lipid peroxidation as well as other oxidative reactions. Ethyl linoleate (EtLA) or 4-hydroxy-2-nonenal (HNE) was reacted with dGuo in the presence of tert-butyl hydroperoxide (t-BuOOH) for 72 h at 50 degrees C. The resulting N(2), 3-epsilonGua was characterized by liquid chromatography/electrospray mass spectroscopy and by gas chromatography/high-resolution mass spectral (GC/HRMS) analysis of its pentafluorobenzyl de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
(49 reference statements)
1
28
0
Order By: Relevance
“…Ham et al showed that N 2 ,N-3 ethenoguanine was formed by direct alkylation following the treatment calf thymus DNA with 13 C-labelled ethyl linoleate under peroxidizing conditions. The authors showed that the level of incorporation of the 13 C label was 86% suggesting that N 2 ,N-3 ethenoguanine was also being formed by an alternative mechanism (169).…”
Section: Quantitation Of Dna Adducts By Lc-msmentioning
confidence: 99%
“…Ham et al showed that N 2 ,N-3 ethenoguanine was formed by direct alkylation following the treatment calf thymus DNA with 13 C-labelled ethyl linoleate under peroxidizing conditions. The authors showed that the level of incorporation of the 13 C label was 86% suggesting that N 2 ,N-3 ethenoguanine was also being formed by an alternative mechanism (169).…”
Section: Quantitation Of Dna Adducts By Lc-msmentioning
confidence: 99%
“…Such oxidative DNA lesions are suspected to be increased with non-DNA reactive chemicals, resulting in the induction of mutations followed by tumor formation. While base oxidation and abasic sites are the most frequent insults to DNA, substantial evidence supports that secondary DNA damage produced from byproducts of primary DNA damage or lipid membrane damage may play an important role in mutation [23,24]. Recently, we have developed ultra sensitive and highly specific mass spectrometric methods for the quantitation of M 1 dG adducts.…”
Section: Introductionmentioning
confidence: 99%
“…52 Previously, the key LPO intermediates that have been identified for the formation of DNA adducts 19,58-60 are the result of reactions of HNE, ONE and MDA with dG and are associated with DNA adducts formed by VC exposure. 58 …”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that the source leading to the formation of 7-OEG was lipid peroxidation and present data to support our hypothesis. The reaction of calf thymus DNA (CtDNA) with [ 13 C 18 ]-ethyl linoleate (EtLa) under peroxidizing conditions resulted in the formation of [ 13 C 2 ]-7-OEG, 52 which could be quantified by LC/MS-MS (Figure 3). In addition to quantitating endogenous and exogenous 7-OEG after [ 13 C 2 ]-VC exposures, the half-life of [ 13 C 2 ]-7-OEG in liver and lung was determined.…”
Section: Introductionmentioning
confidence: 99%